KINEMATIC DIFFERENCES BETWEEN PROFICIENT AND NON-PROFICIENT FREE THROW SHOOTERS – VIDEO ANALYSIS - Dimitrije Cabarkapa; Andrew C. Fry; John P. Poggio; Michael A. Deane (Journal of Applied Sports Sciences, 2021)
Despite its importance and significant contribution to the final game out-come, the free throw shooting motion is greatly understudied. The purpose of this study was to examine kinematic differences between proficient and non-proficient free throw shooters and to determine which variables have the greatest impact on successful free throw shooting performance. Thirteen healthy recreationally active males volunteered to participate in this study. Each participant shot three sets of ten consecutive free throws from the regulation distance from the basket. Each set was performed under 3 minutes with 1-2-minute rest between each set. A high-definition camera recording at 30 fps captured the free throw shooting motion from a sagittal point of view. Video analysis software was used to analyze the following kinematic variables: knee angle, elbow angle, hip flexion, ankle flexion, release angle, shoulder angle, hand release height, and elbow height. The findings of this study suggest that lower elbow positioning influenced by greater knee, ankle, and hip flexion during the preparatory phase of the shooting motion may lead to improvements in free throw shooting accuracy. Moreover, greater ball release height and release angle, as previously suggested, could decrease the margin of error and enhance free throw shooting performance. By using these kinematic variables to create the discriminant function projection model, it is plausible that proficient free throw shooters can be accurately classified in 94% of cases.